Indigenous Peoples' Innovation: Intellectual Property Pathways to Development - Drahos, Peter (ANU Press, 2012)
Traditional knowledge systems are also innovation systems. This book analyses the relationship between intellectual property and Indigenous innovation. The contributors come from different disciplinary backgrounds including law, ethnobotany and science.